Internalized stigma in mental health staff with lived experience of mental crises–Does the professional role protect against self-stigmatization? - Stuetzle, Stefan; Brieger, Anna; Lust, Christian; Ponew, Angel; Speerforck, Sven; von Peter, Sebastian (Frontiers in Psychiatry, 2023)
Objective: The stigma of mental illness is widespread in the general population and also among healthcare and psychiatric professionals. Yet, research on the self-stigma of the latter is still limited. The purpose of this article was to assess self-stigma and its correlates in mental health professionals with lived experiences of mental crisis and treatment. Methods: In a cross-sectional exploratory research project, 182 mental health professionals with lived experiences of mental crisis and treatment from 18 psychiatric hospital departments in the German federal states of Berlin and Brandenburg were surveyed on their lived experiences, self-stigma, perceived stigma in the workplace, subjective vulnerability to crises, and meaningfulness of lived experiences. To investigate the relationships between the variables, manifest and latent correlation analyses were calculated. Results: Results showed low levels of self-stigma and perceived public stigma in the workplace. Self-stigma was significantly and positively associated with workplace stigma and subjective vulnerability to crisis, but not with identification with lived experiences. Conclusions: The relationship between self-stigma, workplace stigma, and vulnerability should be investigated in terms of mutual causality in order to derive possible strategies of reducing self-stigma along with its detrimental effects. Possible reasons for the low levels of self-stigma are discussed in the light of limitations, including processes of self-selection, with highly self-stigmatizing individuals being possibly discouraged from participating. Strategies to enhance sampling quality are briefly discussed.